Implementation of Criminal Sanctions for Corporate Crimes - Yoviza, Yoviza (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2024)
Law enforcement against corporate crime is an issue that receives serious attention in an effort to maintain justice at the corporate level. The imposition of criminal sanctions against corporate crime is the main strategy in suppressing illegal behavior among companies. This article discusses the relevance, effectiveness, and implications of the imposition of criminal sanctions against corporate crime. The application of criminal sanctions aims to create clear responsability among perpetrators of corporate crime. By threatening companies and individuals within them with serious legal consequences, criminal sanctions become an important instrument to encourage compliance with the law and ethical business practices. In addition, criminal sanctions also act as a deterrence factor, as the potential for harsh penalties can reduce incentives to engage in illegal behavior. However, the enforcement of criminal sanctions has also generated some debate. Some parties are concerned that sanctions that are too severe can harm the company excessively, even to the point of potentially causing harm to employees who are not directly involved in the crime. Therefore, it is necessary to enforce sanctions that are balanced with the crime committed, taking into account factors such as the level of loss caused, the responsibility of individuals within the company, and the extent to which the company has tried to prevent crime. In addition, law enforcement against corporate crime must be accompanied by other efforts, such as increasing transparency, establishing stricter policies, and empowering oversight institutions. The combination of these various approaches can form a more effective system in preventing and cracking down on corporate crime. Overall, the imposition of criminal sanctions against corporate crime is an important step in ensuring corporate and individual accountability for their actions. However, it is important to maintain a balance between strict law enforcement and the protection of individual rights and the overall sustainability of the company. Only with a comprehensive and balanced approach can society fight corporate crime and encourage fairer and more responsible business practices.